Ceramide-Induced Cell Death Depends on Calcium and Caspase-Like Activity in Rice - Zhang, Quan-Fang; Li, Jian; Bi, Fang-Cheng; Liu, Zhe; Chang, Zhen-Yi; Wang, Ling-Yan; Huang, Li-Qun; Yao, Nan (Frontiers in Plant Science, 2020)
Ceramide sphingolipids are major components of membranes. C2 and C6 ceramides induce programmed cell death (PCD) in animals and plants and we previously showed that C2 and C6 ceramides induce PCD in rice (Oryza sativa) protoplasts. However, the mechanistic link between sphingolipids and PCD in rice remains unclear. Here, we provide evidenceobserved that calcium levels increased rapidly after ceramide treatment.; Moreover, the calcium channel inhibitor LaCl3 and the intracellular calcium chelator acetoxymethyl-1, 2-bis (2-aminophenoxy) ethic acid (BAPTA-AM) inhibited this calcium increase and prevented ceramide-induced PCD. Moreover, caspase-3-like proteasethe activity of caspase-3 like protease increased significantly in C6 ceramide-treated protoplasts and a caspase-specific inhibitor prevented C6 ceramide-induced cell death. We also detected the other typical sequential diagnostic PCD events; including ATP loss. andDIDS (4, 49-diisothiocyanatostilbene- 2, 29-disulfonic acid), the an inhibitor of voltage-dependent anion channels (VDAC), DIDS can inhibitor thedecreased C6 ceramide-induced cell death. Together, this These evidences suggests that mitochondrial played an important role in C6 ceramide-induced PCD.